The relative DNA-shedding propensity of the palm and finger surfaces. Issue 5 (September 2015) - Oleiwi, A.A.; Morris, M.R.; Schmerer, W.M.; Sutton, R.
Abstract: The relative DNA shedding propensity of palmar and finger surfaces has not previously been examined. In the study presented here, palm and fingermarks of six volunteers were analysed for DNA recovery, after deposition at a pressure of approximately 4900 Pa onto glass plates or slides, respectively. The marks were swabbed; DNA extracted using a modified Chelex® method, and then quantified using qPCR, followed by genotype analysis. To assess the availability of DNA-containing material on the skin surface, DNA was analysed by directly swabbing the palm and fingerprint areas of the skin. A further set of palm and fingermarks was subjected to microscopic examination. The results demonstrated that the quantity of DNA shed from the palmar surface is significantly less than from two fingers. Single donor DNA profiles were obtained from deposited fingermarks by applying a low copy number protocol (32 cycles). DNA retrieved from palm and fingers may be degraded, as suggested by reduced peak intensity and allelic dropout amongst the larger STR loci. These findings suggest that, owing to the low levels of DNA deposition, when palmar marks are found at crime scenes, every effort should be made to recover friction ridge detail to use as an identification metric, with collection for DNA analysis performed afterwards. Highlights: The palm sheds a significantly lower amount of DNA than the finger. DNA contained in finger and palm marks may be degraded. Compared both; within and between donors, each deposition of finger or palm mark may yield in highly variable amounts of DNA.